Ferroptosis in diabetic retinopathy: from pathogenic mechanisms to translational prospects - Jiang, Jieyu; Liu, Zhimin; Chen, Xiangdong (Frontiers in Endocrinology, 2026)
Diabetic retinopathy (DR) is a common microvascular complication of diabetes. Despite ongoing revisions in the prevention and treatment of DR, optimal treatment strategies have yet to be established. Revealing the pathological changes and molecular mechanisms of DR is the cornerstone for exploring new therapeutic strategies. Ferroptosis, a new type of programmed cell death proposed in recent years, is characterized mainly by reactive oxygen species and iron-mediated lipid peroxidation. As studies progress, growing evidence has highlighted the involvement of ferroptosis, a newly identified programmed cell death pathway, in the development and pathological mechanisms of DR. The purpose of this review is to discuss the known underlying mechanisms of ferroptosis and elucidate its role in the pathogenesis of DR. Additionally, it explores the abnormal manifestations of iron metabolism and related signaling pathways in DR. Finally, we also summarize the potential compounds that may act as ferroptosis inhibitors in DR in the future. By synthesizing these aspects, this review aims to provide insights for a deeper understanding of the relationship between ferroptosis and DR, as well as potential prevention and treatment strategies.